PGV-PII - Szawerna, Maria Irena; Suchardt, Jacob Lee (University of Gothenburg, 2025)
This is a small corpus of 10 pairs of texts in Swedish and English annotated with personal information categories. The annotation largely follows that of the TAB corpus (https://aclanthology.org/2022.cl-4.19/). The twenty texts in total were sourced from the Parallel Global Voices corpus (https://nlp.ilsp.gr/pgv/, CC BY 4.0) and manually annotated. That corpus, in turn, had collected the texts from the Global Voices websites (https://globalvoices.org/, CC BY 3.0).

Det här är en liten korpus som består av 10 par texter på svenska och engelska, annoterade med kategorier av personliga uppgifter. Annoteringen liknar den av TAB-korpusen (https://aclanthology.org/2022.cl-4.19/). De tjugo texterna har sitt ursprung i Parallel Global Voices-korpusen (https://nlp.ilsp.gr/pgv/, CC BY 4.0) och var annoterade för hand. Denna korpus innehåller data från Global Voices-webbsidorna (https://globalvoices.org/, CC BY 3.0).
PGV-PII
Keywords: Language Technology (Computational Linguistics); pseudonymization; anonymization; parallel; news; corpus; Natural Language Processing; Språkbehandling och datorlingvistik